Prevalence and associated factors of healthy aging among community-dwelling older adults in Lishui city, China: a cross-sectional study - Jian-Hua Chen; Norhasmah Mohd Zain; Azlina Yusuf; Bi-He Ying (BMC Public Health)
Abstract Background Identifying the level of healthy aging and exploring its associated factors are prerequisites in the planning of effective measures among the elderly population. Thus, this study aimed to investigate the prevalence of healthy aging and determine its associated factors among community-dwelling older adults from mountain areas in Lishui, China. Methods A multicenter cross-sectional survey was conducted. Participants were recruited by a multi-stage stratified cluster-sampling procedure from a mountainous region in Lishui City, Zhejiang Province, China. A validated questionnaire of Healthy Aging Instruments (HAI), Basic Psychological Needs Satisfaction (BPNS), Patient Health Questionnaire (PHQ-9), Ascertain Dementia 8 questionnaire (AD8), Family Adaption Scale (FAS), Community-Based Health Promotion Activity Questionnaires (HPAQ), Social Function Questionnaire for Chinese Older Adults (SFQCOA), Adult Health Self-Management Skills (ability) Rating Scale (AHSMSRS) was incorporated. The questionnaire also captured sociodemographic characteristics, lifestyle behaviors, and Self-Perceived Healthy Ageing (SPHA). Multivariate stepwise linear regression analysis was performed. Results The mean score of the Healthy Aging index was 136.5 (18.22). The majority of the participants have a high level of healthy aging (65.5%). Regression analysis showed 12 predictors of healthy aging: self-perceived economic independence, lifestyle-related behaviors, subjective physical health, psychological health, better competence of BPNS, frequency of community-based HPA participation, lower HPA-perceived barriers, social support, social engagement, and Health Self-Management (HSM) ability with two dimensions HSM-Consciousness and HSM-Behavior, as well as SPHA (P < 0.05). Conclusions This study contributed to the existing gap in both subjective and objective understanding of healthy aging, especially in terms of its relationship with sociodemographic factors, lifestyle-related behaviors, individual health conditions, environmental coverage, as well as family, community and social support. Both individual-environment interaction factors as better HSM ability as well as SPHA might help predict older adults’ healthy aging in mountainous areas in China. Developing an accurate, reliable health promotion program that provides insights may improve healthy aging changes in mountainous regions for community healthcare staff, especially nurses.